Methotrexate induced neutropenia: A case report - Ahmed, Syed Mozaffor; Salek, AK Mohammed; Ahsanullah, Md; Hasan, Suzon Al (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v18i2.3837 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):47-48